"Análisis e implementación de un sistema de manejo de incidentes con funcionalidad extendida notificación de correo electrónico bajo Gnu/Linux aplicado a los servidores y enlaces Lan y Wan de la empresa Edesa S.A.". - Barriga Martínez, Edison Lenin (2013)
Implementing a monitoring and ticketing system to keep better track of network problems. For a network administrator is very important to stay informed of the behavior of both network links Wan Lan as well as having a history of performing work as meoria to solve future problems quickly and effectively. Nagios will allow the administrator apprised of the status of the links and servers by sending email alerts to members of the department of information technology (IT) to address likely cuts in service provided by the company.